Alberta Bounded: Comprehensive Sexual Health Education, Parentism, and Gaps in Provincial Legislation and Educational Policy - Grace, Andre P (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
This article makes a case for mandating comprehensive sexual health education (CSHE) for all students in Canadian schooling, with a focus on Grades 7 to 12. Using Alberta as an example, it examines the degree to which legislation and educational policy enable CSHE, with particular attention to sexual and gender minority (SGM) students. The article conceptualizes and interrogates parentism as a rightist politico-religious viewpoint harmful to high school students needing to build sexual knowledge and sexual agency. It concludes by calling on legislators, school districts, and faculties of education to act to enable CSHE for all students, including SGM students.